Teachers’ strategies in teaching English grammar in a private high school in Yogyakarta: A qualitative inquiry - Sorohiti, Maryam; Putri, Devika; Suryanto, Jati; Osman, Nazira (Universitas Muhammadiyah Yogyakarta, 2026)
This study explores the strategies used by English teachers in teaching grammar in private senior high schools in Yogyakarta. Using a qualitative descriptive approach, the study investigated the teachers’ pedagogical techniques, classroom practices, and beliefs underlying grammar teaching. Data were collected through in-depth interviews, classroom observations, and document analysis involving six English teachers. Findings indicated that teachers integrate inductive and deductive approaches, contextualize grammar teaching through real-life communicative tasks, and use technology to enhance student engagement. Furthermore, teachers demonstrated adaptive strategies in responding to students’ needs and curriculum demands. This study provides implications for grammar pedagogy in the Indonesian EFL context and contributes to professional development by highlighting reflective and context-sensitive teaching practises.